Agents of Integration : Understanding Transfer as a Rhetorical Act - Nowacek, Rebecca S. (Book collections on Project MUSE., 2011)
The question of how students transfer knowledge is an important one, as it addresses the larger issue of the educational experience. In Agents of Integration: Understanding Transfer as a Rhetorical Act, Rebecca S. Nowacek explores, through a series of case studies, the issue of transfer by asking what in an educational setting engages students to become "agents of integration"--Individuals actively working to perceive, as well as to convey effectively to others, the connections they make. While many studies of transfer are longitudinal, with data collected over several years, Nowacek's is sync